PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH KUR PADA PT. BANK MANDIRI (PERSERO) TBK KC MANADO DOTULOLONG LASUT - Esther Nova Kila; Paulus Adrian Pangemanan; Ellen Grace Tangkere (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine how satisfaction of customer of KUR PT. Bank Mandiri (Persero) Tbk KC Manado Dotulolong Lasut for five service quality variables.The research was conducted for four months from September to December 2016.The method used is the survey method throught direct interviews with 100 respondents who are KUR customers using descriptive analysis based on the Likert Scale. The results of the study show that service quality is shown through the level of satisfaction of KUR customers at PT. Bank Mandiri KC Manado Dotulolong Lasut is classified as very satisfied which is measured based on five variables, namely tangible, reliability, responsiveness, assurance, and empathy.*jnkd+eprm*